Free trade and implications for hunger - Dos Santos, Maria José Palma Lampreia (2020)
Free Trade are the numerous forms of elimination of trade barriers among regions on the world. Usually they the intent to eliminate the trade barriers by the construction of trade agreements that usually allow various types of international economic integration agreements, namely, free trade agreements, customs unions, common markets, and economic unions, etc. This paper refers to the elimination of barriers among countries and regions on trade mainly in countries in development promote the economic development by bringing new countries with competitive advantages to the international commerce. Also, new innovative techniques of production foods are referred, as aquaponics production in order to contribute to zero hunger. As a consequence, the international supply of food generally increases at the beginning the prices decrease and allow to increase the demand of food, that means a construction, in ceteris paribus of a new market equilibrium higher than the initial that will contribute for food security and for the reduction of hunger around the world. This is also one of the Sustainable Goals from United Nations to achieve.